Gender differences in physical activity and sedentary behavior: Results from over 200,000 Latin-American children and adolescents. - Javier Brazo-Sayavera (PLoS ONE, 2021)
More physical activity and less sedentary behavior is beneficial for children and adolescents. Worldwide, gender differences are >8% favorable for men and the Latin-American region presents an even higher level of insufficient physical activity among women, with a lack of information in young population. Thus, the aim of the current study was to describe the gender differences in physical activity and recreational sedentary behavior in children and adolescents from Latin-American countries. The targeted age range was 5 to 17 years and included 219,803 participants (106,698 boys and 113,105 girls) from 33 out of 47 Latin-American countries identified. Physical activity guidelines from the World Health Organization (≥60 minutes of moderate-to-vigorous physical activity seven days of the week) and <3 hours recreational sedentary behavior daily were the references. In general, boys showed a higher prevalence of meeting physical activity guidelines in comparison with girls. A higher proportion of girls met the <3 hours recreational sedentary behavior cut-point in only ten countries. Thirty percent of the identified countries had no available data. The majority had data from the Global School-based Student Health Survey with data principally on adolescents and only 11/33 countries reported data in the last 5-year period. In conclusion, gender differences in the compliance with physical activity guidelines and the <3 hours recreational sedentary behavior cut-point are evident among children and adolescents from Latin-American countries, with boys being more active than girls.